2002
DOI: 10.1902/jop.2002.73.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Periodontitis: 5‐Year Follow‐Up of Treatment

Abstract: In aggressive periodontitis, comprehensive mechanical/surgical and antimicrobial therapy is an appropriate treatment regimen for long-term stabilization of periodontal health. In this study, periodontal disease progression was successfully arrested in 95% of the initially compromised lesions, while 2% to 5% experienced discrete or recurrent episodes of loss of periodontal support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 26 publications
2
78
1
6
Order By: Relevance
“…In the PG group, the intrabony defect was filled with the bioactive glass granulate, to which 8 to 12 drops of 0.9% NaCl solution per cm had been added. 3 After a mixing time of 10 to 15 seconds, the resulting cohesive mass was processed within two to three minutes (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In the PG group, the intrabony defect was filled with the bioactive glass granulate, to which 8 to 12 drops of 0.9% NaCl solution per cm had been added. 3 After a mixing time of 10 to 15 seconds, the resulting cohesive mass was processed within two to three minutes (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study which included 48 patients with early-onset periodontitis (EOP), reported an AL of 0.03-0.35 mm around the affected teeth after 4 years (26). AgP patients with a well-maintained therapy manifested 2.2% sites with an AL of ≥2 mm (27). The annual TL of treated AgP (or EOP) patients varied from 0.08-0.24 per patient (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Studies agree that treatment should be supplemented with antibiotics (53) . The objectives of the treatment are the same as for chronic periodontitis: reducing or eliminating the bacterial load and the contributory risk factors, in addition to regenerating the attachment apparatus as soon as possible.…”
Section: Abilitymentioning
confidence: 99%
“… Study, diagnosis and treatment of occlusal disharmony and temporomandibular disorders (4)  Taking bacterial samples from selected pockets, cultures and antibiotic sensitivity testing can also be considered (4)  Prior dental treatments, if necessary  Supragingival and subgingival scaling and root planing. Mechanical therapy is key in the treatment of aggressive periodontitis (4,53) . Even current consensus is that antimicrobial therapy should be preceded by mechanical debridement to break the structure of the biofilm (54) .…”
Section: Abilitymentioning
confidence: 99%
See 1 more Smart Citation